Non-immunogenicity of enucleated rat hepatoma cells in syngeneic animals. - Gerlier, D. (Nature Publishing Group, 1981)
Cytoplasts and karyoplasts were obtained by ultracentrifugation of Hepatoma D23 cells on a Ficoll gradient containing cytochalasin B. Their nuclear and protein content and their metabolic activity were determined. Three i.p. injections of 2.3 x 10(7) cytoplasts were unable to protect syngeneic WAB/Not rats against an s.c. challenge of 10(4) D23 cells, whereas a similar amount of karyoplasts, or 3 injections of 10(6) irradiated D23 cells, were fully protective. Ability of cytoplasts to act as primary or secondary immunogen were also studied, and compared to that of 0.01% glutaraldehyde-treated cells, 43 degrees C heat-treated cells and 3M KCl-soluble extracts, these preparations also being of weak immunogenicity. Only heat-treated cells behaved as a primary immunogen, whereas none of the preparations provided a secondary stimulation. Moreover, when these preparations were fed in vitro to peritoneal-exudate cells before their injection into rats, cytoplasts and glutaraldehyde-treated cells showed no immunogenicity, whereas heat-treated cells induced full protection against tumour challenge. Therefore, in this tumour model, the in vivo persistence of immunogen and the presence of a nucleus are likely to be crucial in inducing transplantation resistance to tumour.